2020
DOI: 10.1093/jpids/piaa030
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Factors Associated With Virological Treatment Failure Among Children and Adolescents on Antiretroviral Therapy Attending HIV/AIDS Care and Treatment Clinics in Dodoma Municipality, Central Tanzania

Abstract: Background As the World Health Organization (WHO) and its joint partners such as USAIDS target achieving 90% sustained virological suppression among children and adolescents living with Human Immunodeficience Virus (HIV)/AIDS, it is imperative to elucidate the current prevalence and factors associated with virological treatment failure for formulation of appropriate strategies. This study was conducted determine the prevalence and factors associated with virological treatment failure among ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
48
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(62 citation statements)
references
References 38 publications
4
48
1
1
Order By: Relevance
“…Our findings revealed that the odds value of virological failure among HIV-infected children with non-disclosure was 4.26 times more compared to those children with disclosed HIV status. This result was consistent with other studies done in Tanzania 17 which revealed that full disclosure of HIV status for children was associated with a protective effect against virological failure and Dodoma municipal 22 which showed that non-disclosed children were 7.74 times more likely to have virological failure than those compared with those disclosed. The result is also in line with the study conducted in Ethiopia 15 , 19 which showed for a checkup that disclosure of HIV status was found to be preventive to virological failure.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Our findings revealed that the odds value of virological failure among HIV-infected children with non-disclosure was 4.26 times more compared to those children with disclosed HIV status. This result was consistent with other studies done in Tanzania 17 which revealed that full disclosure of HIV status for children was associated with a protective effect against virological failure and Dodoma municipal 22 which showed that non-disclosed children were 7.74 times more likely to have virological failure than those compared with those disclosed. The result is also in line with the study conducted in Ethiopia 15 , 19 which showed for a checkup that disclosure of HIV status was found to be preventive to virological failure.…”
Section: Discussionsupporting
confidence: 92%
“…In this study, children who had a history of poor adherence were 6.05 times more likely to develop virological 36 which showed that poor adherence increases the odds value of virological failure and Malawi 21 which revealed that a high percentage of virological failure was due to poor adherence. The study was also in line with the study done in Dodoma municipal, 22 Tanzania, 32 and Senegal, 13 Wollo. 37 This might be due to poor adherence causing periodic viral replication that result in the development of drug resistance and limited treatment outcomes.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…This study is supported by similar finding reported in Tanzania. 36 Disclosure of status is positively associated with better social support, stronger family and relationship cohesion, and reductions in anxiety and depression. This leads to improvements in physical health, emotional support, and financial support which leads to HAART adherence.…”
Section: Discussionmentioning
confidence: 99%